Built Environment and Frailty: Neighborhood Perceptions and Associations With Frailty, Experience From the Nagoya Longitudinal Study. (June 2021) - Martins, Beatriz A.; Visvanathan, Renuka; Barrie, Helen R.; Huang, Chi Hsien; Matsushita, Eiji; Okada, Kiwako; Satake, Shosuke; Edwards, Suzanne; Uno, Chiharu; Kuzuya, Masafumi
Neighborhood physical characteristics have been consistently associated with the health of older adults. This article investigates links between frailty and perceptions of the neighborhood environment. Using a cross-sectional analysis of 370 community-dwelling older adults from Nagoya, Japan, neighborhood perceptions were assessed using the Neighborhood Environmental Walkability Scale (NEWS) in addition to frailty, using a frailty index. Frailty was associated with the NEWS composite index, land use mix diversity, land use mix access, street connectivity, walking infrastructure, aesthetics, and crime safety, after adjustment for covariates. Older adults with increasing frailty have poorer perceptions of their neighborhoods, which could lead to further constriction of the life-space, less social and physical engagement, and worsening of frailty status.